Psychometric validation of an instrument for measuring patient experiences with outpatient healthcare - Sočan, Gregor (Zdravstveno varstvo, 2023)
Aim: Recently, a patient-reported experience measure (PREM) was developed in Slovenia to assess patients’ experiences with outpatient specialist healthcare clinics. The aim of this study was to evaluate the psychometric properties (including factor structure, reliability, convergent validity, and response distribution) of the questionnaire. Methods: The sample consisted of 8,406 adult participants treated in 171 specialist clinics from different medical fields. Participants voluntarily and anonymously responded to either the paper or online survey. Results: Descriptive statistics show meaningful response patterns with a general tendency towards favourable assessments. The psychometric analyses of the scales evaluating doctor’s and nurses’ work, respectively, generally showed a good fit of the unidimensional factor model as well as the Rasch model, high factor loadings and very good to satisfactory reliability. The Rasch scaling showed that these scales were most informative for patients with relatively unfavourable experience ratings. Conclusions: The results are similar to those found in previous evaluations of PREMs in other countries. Given its good psychometric properties, the Slovenian PREM can be recommended for healthcare evaluations in Slovenia and as a model for the development of similar PREMs in other countries.
Keywords: factor analysis; faktorska analiza; merjenje izkušenj pacientov; patient reported experience measures; reliability; Slovenia; Slovenija; validity; veljavnost; zanesljivost